theorem zfstsndeq0 (n: nat): $ zfst n = 0 /\ zsnd n = 0 <-> n = 0 $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
zfst n -ZN zsnd n = n |
||
2 |
0 -ZN 0 = 0 |
||
3 |
zfst n = 0 /\ zsnd n = 0 -> zfst n = 0 |
||
4 |
zfst n = 0 /\ zsnd n = 0 -> zsnd n = 0 |
||
5 |
zfst n = 0 /\ zsnd n = 0 -> zfst n -ZN zsnd n = 0 -ZN 0 |
||
6 |
zfst n = 0 /\ zsnd n = 0 -> zfst n -ZN zsnd n = 0 |
||
7 |
zfst n = 0 /\ zsnd n = 0 -> n = 0 |
||
8 |
zfst 0 = 0 |
||
9 |
n = 0 -> zfst n = zfst 0 |
||
10 |
n = 0 -> zfst n = 0 |
||
11 |
zsnd 0 = 0 |
||
12 |
n = 0 -> zsnd n = zsnd 0 |
||
13 |
n = 0 -> zsnd n = 0 |
||
14 |
n = 0 -> zfst n = 0 /\ zsnd n = 0 |
||
15 |
zfst n = 0 /\ zsnd n = 0 <-> n = 0 |